Pregnancy-Related and Neonatal Outcomes during Omicron Variant-Dominant COVID-19 Pandemic among the Black-Dominant Population - Min, Daniel D.; Min, Jae H. (American Journal of Perinatology, 2024)
Objective This study aimed to determine the effect of the Omicron variant on pregnancy-related and neonatal outcomes among the Black-dominant population.Study Design We performed a single-center, retrospective cohort study during the prepandemic period from December 1, 2019, to February 29, 2020, and the Omicron surging period from December 1, 2021, to February 28, 2022. A total of 518 pregnant women were admitted for delivery during the study period. Multiple gestations (n = 21) and deliveries at less than 20 weeks of gestation (n = 5) were excluded. We analyzed and compared the sociodemographic and clinical data from mothers and their neonates between the two cohorts as well as between severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) positive and negative mothers during the Omicron surge. Subgroup analyses were also conducted specifically among the Black-only population.Results The cohorts were predominantly Black (88.6%), with smaller proportions of Hispanic (8.9%), Asian (0.8%), White (0.8%), and other ethnicities (0.8%). Of 492 singleton deliveries, 275 live births, 8 (2.8%) stillbirths, and 31 (11.3%) preterm births (PTBs) occurred during the prepandemic period, and 207 live births, 2 (1%) stillbirths, and 33 (15.9%) PTBs occurred during the Omicron wave. There was no statistically significant difference in the rates of PTBs, stillbirths, medically indicated PTBs, and cesarean delivery between the two cohorts. SARS-CoV-2-positive mothers were not at an increased risk of adverse outcomes. However, neonatal intensive care unit (NICU) admission rate significantly increased among neonates born to SARS-CoV-2 positive mothers compared with negative mothers (32.3 vs. 16.5%, p = 0.038). In subgroup analyses among Black individuals, this difference was not observed.Conclusion There was no significant difference in pregnancy-related or neonatal outcomes in the Black-dominant population between the two cohorts. SARS-CoV-2 infection did not alter these findings except for an increased NICU admission rate among neonates born to SARS-CoV-2-positive mothers.Key Points
Keywords: COVID-19; Omicron; Black-dominant population; neonatal outcome; pregnancy outcome